Perancangan Video Mapping Sebagai Media Pengenalan Topeng Malangan - Alfi Syahrin; Subari Subari; Achmad Zakiy Ramadhan (MAVIS : Jurnal Desain Komunikasi Visual, 2020)
The richness of literary performances in Indonesia is very diverse. The diversity that exists is wealth that can not be calculated in value. Regional culture is reflected in various aspects of existing community life, because each region has different cultural characteristics. This culture needs to be preserved so as not to decrease or even disappear. Malang Mask has become one of the high artistic value cultural heritages in Malang. The community must be familiar with the arts of this area in order to maintain culture. However, people now if you look at culture with a traditional display it will be difficult to attract their attention. In the design process it is necessary to analyze data, primary data sources and secondary data sources. The next step is to draw conclusions from the results of the data obtained. After the conclusion is obtained next is to determine the concept based on the results of the data conclusions. The methodology used is to use the 5w + 1H approach which is used as a basis for the concept of problem solving, which consists of What, Who, When, Where, Why, and How. The purpose of the 5W + 1H analysis is to get the video mapping design concept that will be produced. This video mapping media showcases culture with a modern concept, Malang Mask characters will be the content in this video. This video mapping will be an installation that uses 3D fields as objects to be projected. This media is also supported by poster media, infographics, t-shirts, totebags, social media and key chains. It is hoped that the "Rawat Raut" video mapping design can help introduce and preserve Malang Mask culture.